FORMULATION FOR THE MAKING OF JAMBLANG (Syzigium cumini L.) LEAF ETHANOL EXTRACT SHAMPOO COMING FROM MANGALLEKANA VILLAGE, MAROS REGENCY - Ririn Dian Sari, Ririn Dian Sari (Journal of Holistic and Traditional Medicine, 2021)
Jamblang leaves (Syzigium cumini L.) is one of the plants that is very step in the season but only a few people know that one of these plant parts can be processed as a shampoo, when the jamblang leaves take place in the management process it is often discarded because the community sometimes do not know the benefits contained in jamblang leaves (Syzigium cumini L.). Jamblang (Syzigium cumini L.) leaves extract can affect the physical properties of the shampoo. This research was conducted by making shampoo from jamblang leaf extract in the manufacture of jamblang leaf extract (Syzigium cumini L.) as an active substance with each different concentration formula, F1 5%, F2 7%, F3 10%. Evaluation of jamblang leaves extract (Syzigium cumini L.) conducted was organoleptic test, homogeneity test, pH test, and foam stability test. The results showed that the results of organoleptic testing on FI had a rather thick shape, characteristic odor, green color, F2 the shape is rather thick typical odor and green +, F3 is rather liquid form, characteristic odor, green color ++, while the homogeneity testing of F1, F2 and F3 shampoo is not homogeneity. Testing the pH on F1 and F2 5 while F3 is 7. Testing the stability of the foam on F1, F2, and F3 = 5 cm.